Contribution to the definition of the metabolic profile of farmed rainbow trout (Oncorhynchus mykiss) - Massimo Mecatti (Italian Journal of Animal Science, 2010)
The haematic outline of 339 rainbow trout (Oncorhynchus mykiss)from two different farms in the Lucca province was studied for a preliminary assessment of the metabolic profile of this species and for the investigation of the influence of some endogenous and exogenous factors on the variability of the studied parameters. The sampling time, as well as the weight, appears to have caused significant variations on most of the parameters analysed. The present study gives the annual means and the seasonal trends for each farm where the study was carried out.